Sex-related differences in the sagittal plane spinal angles in preschool and school-age children - Labecka Marta Kinga (Sciendo, 2022)
Study aim: The study aimed to assess the differences in the magnitude of the anterior-posterior spinal curvatures depending on sex in children aged 5 and 9 years.